Estimation of Carbon Reserves of Seagrass Enhalus acoroides in Balikpapan Bay Waters of East Kalimantan Province - Nababan, Magdalena Maslita; Sari, Lily Inderia; Irawan, Aditya (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
The research was conducted from October 2022 – January 2023 in the waters of Balikpapan Bay, East Kalimantan Province. The purpose of this study was to determine the estimated carbon content of seagrass E. acoroides in the Balikpapan Bay Waters.  The results showed that the density of E. acoroides ± 501 stands/m2 belonged to the very tight category.  Biomass stored in the waters of Balikpapan Bay is the above substrate part of 592.54 g/m2, and the biomass in the below substrate part is 1218.57 g/m2.  The estimated carbon storage at the above of the substrate is 264,32 gC/m2 and the value at the below of the substrate has a carbon value of 608,50 gC/m2.